Estudo das vilosidades em segmentos do intestino de ratos após a confecção de esfíncteres - Angela Aparecida Barra (2007)
When the handles of the small bowel are submitted to surgical traumas with resection of a segment significant changes occur in the mucous layer. This research tried to identify the reactions of the villus in intestinal segments of rats underwent the confection of sphincters. Male Wistars adult rats, had been distributed among three groups of 10 animals. In control group (A) had been removed a segment of the distal intestine for comparison with the operated groups. In group (B) at 100 millimeters and 150 millimeters from the ileocecal junction had been performed two located sphincters. In group (C) had been performed only one sphincter 100 millimeters from the ileocecal junction. Between 10th and 14th days the animals had been reoperated for withdrawal of intestinal segment involving the sphincters. The animals had been weighted before the two operations. The intestinal caliber had been measured during both the surgical procedures. Villus height had been achieved during histological examination through morfometry of the several segments. In group B that had been carried out before the proximal sphincter, after the distal sphincter and at the intermediate segment. In group C had been carried out at pre and postsphincter segments, meanwhile in group A villus height were considered the normal parameter. The results had shown an increase of the villus height in the segments before proximal sphincter and after distal sphincter in group B as well as in the pre and postsphincter segments in group C, when compared with the control group. No histologic changes had been observed at the intermediate segment in group B. The animals of both the groups had presented body weight and an increase of the handles diameter.